1988
DOI: 10.1002/chin.198848357
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Calamitic Liquid Crystals by Transition Metal Catalyzed Cross‐Coupling Reaction

Abstract: ChemInform Abstract (63 refs.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The detailed investigations of the reaction conditions of the preparation of substituted cyclohex-2-enones have shown that the mesomorphic 3,6-disubstituted cyclohex-2enones (11) with different combinations of cyclic, bridge, terminal fragments and lateral substituents can be prepared in a yield 60-80% and in a short way by the condensation of the corresponding Mannich salts or 2-chloro(bromo)ethylaryl(alkyl)-ketones with 2-substituted acetoacetic esters, 4substituted methyl-benzylketones, or analogous ketones and β-dicarbonylic compounds in the presence of potassium carbonate, potassium hydroxide and phase catalysts in a boiling diglyme or dioxane. 32,33 For example, the 3,6-disubstituted cyclohex-2-enones of the following structures (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) have been prepared using these starting materials and the reaction conditions. n, m = 1-10; Y 1,2,3,4 = H, F, Cl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed investigations of the reaction conditions of the preparation of substituted cyclohex-2-enones have shown that the mesomorphic 3,6-disubstituted cyclohex-2enones (11) with different combinations of cyclic, bridge, terminal fragments and lateral substituents can be prepared in a yield 60-80% and in a short way by the condensation of the corresponding Mannich salts or 2-chloro(bromo)ethylaryl(alkyl)-ketones with 2-substituted acetoacetic esters, 4substituted methyl-benzylketones, or analogous ketones and β-dicarbonylic compounds in the presence of potassium carbonate, potassium hydroxide and phase catalysts in a boiling diglyme or dioxane. 32,33 For example, the 3,6-disubstituted cyclohex-2-enones of the following structures (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) have been prepared using these starting materials and the reaction conditions. n, m = 1-10; Y 1,2,3,4 = H, F, Cl.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17] The LC derivatives of phenylcyclohexane are synthesized using the Nenitzescu method or Grignard reaction. 18 Grignard or the cross-coupling and Friedel-Crafts reactions are also used for the preparation of LC biphenylcyclohexane or biphenyl-cyclohexene derivatives or other three-and four-rings liquid-crystalline compounds; for example, derivatives of dicyclohexylphenyl (4) and 4,4′-dicyclohexylbiphenyl (5), [19][20][21][22] which are very important components of the compositions with a wide temperature range of the nematic phase. Unfortunately, these methods do not allow the synthesise of such compounds with a high yield and without the formation of by-products.…”
Section: Introductionmentioning
confidence: 99%
“…From lots of the 3,6-disubstituted cyclohex-2-enones (I), trans-2,5-disubstituted cyclohexanones (II) and their derivatives, which have been synthesised and investigated, we have to described the following: (A) Substituted cyclohexenes (1, 2, 7; 8a-d), fluorocyclohexenes (9a-d) and fluorocyclohexanes (4,6), which are characterised a low optical anisotropy and viscosity, and a low temperature formation of the nematic phase (Scheme 6; Tables 1 and 2). [30][31][32][33] (B) Lateral substituted p-terphenyls, p-quaterphenyls and p-quinquephenyls (10-17), which, as our investigations have shown [34][35][36][37], are easily formed in a one-stage procedure from the corresponding 3,6-disubstituted cyclohex-2-enones (I.3) (Scheme 7).…”
Section: Synthesis Of Liquid-crystalline and Anisotropic Compoundsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Unfortunately, the methods for the preparation of arylboronic acids, Grignard reagents from 4-bromo-1-(trans-4-alkylcyclohexyl)benzenes or 4-bromo-4-substituted biphenyls and 4-(4-substituted phenyl)cyclohexanones and 4-(trans-4-substituted cyclohexyl)cyclohexanones from the corresponding 4-substituted benzylmethylketones, 1,4-cyclohexanedione, or from the adducts of the condensation of corresponding 2-substituted 1,3-butadienes with 4-substituted styrenes are usually complicated and are characterised by a low yield of the products. [12][13][14] It has been reported that the mesomorphic derivatives of benzene, cyclohexane, biphenyl or terphenyl, which are useful components of LC mixtures for display applications, can be easily prepared in a high yield from the corresponding 3,6-disubstituted cyclohex-2-enones [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%